Analytical modelling of Breathing Walls: experimental verification by means of the Dual Air Vented Thermal Box lab facility. (December 2017) - Alongi, Andrea; Angelotti, Adriana; Mazzarella, Livio
Abstract: Breathing Walls are air permeable envelope components based on porous materials. In contra-flux operation air flows opposite to conductive flux, while in pro-flux they have the same direction. The Breathing Wall behaves either as a ventilation heat exchanger or as an active insulation. In literature an analytical model describing steady state heat transfer across a Breathing Wall can be found. Since it lacks an exhaustive experimental validation, a facility developed at the Energy Department of Politecnico of Milano was used to investigate the thermo-physical behavior of a no-fines concrete based Breathing Wall in steady state Dirichlet conditions and contra-flux operation.